Impact of cluster farming on smallholder farmers teff commercialization in Ethiopia - Birara Endalew; Asres Elias; Kumi Yasunobu (CABI Agriculture and Bioscience)
Abstract Background Cluster farming is an agricultural practice that involves organizing and grouping together farmers within a specific geographic area based on proximity of their farm plots to create synergies and economies of scale. In developing countries including Ethiopia cluster farming has gained prominence as a strategic initiative to foster commercialized agriculture and enhance the livelihoods of smallholder farmers by integrating their production within the broader value chain. In light of this, the government of Ethiopia plans to promote cluster farming throughout the country based on the best practices of the four cluster farming priority regions and 10 high-value commodities. Teff is one of the high-value commodities in the cluster farming priority regions. However, the impact of cluster farming on teff commercialization was not studied before. Methods We conducted this study to examine the impact of cluster farming on teff commercialization using nationally representative data collected by Agricultural Transformation Institute of Ethiopia. Then, we analyzed the data using descriptive and inferential statistics, commercialization index, and endogenous switching regression model. Results The result revealed that the mean teff commercialization of cluster farming participants was higher than non-participants in all the cluster farming priority regions of Ethiopia. Similarly, the model result indicated that cluster farming had a positive and significant impact on teff commercialization at p < 0.01. Conclusion The findings suggest that the promotion of cluster farming facilitates teff commercialization in Ethiopia. However, we recommend further studies using panel data collected from large samples to provide a longitudinal perspective on the impact of cluster farming on teff commercialization over time. The findings of these studies can offer comprehensive insights and concrete information that can inform policymakers to support and promote teff cluster farming in Ethiopia.